Method for intensively leaching lithium in low-grade refractory lepidolite through full wet process

Through the full wet method to strengthen the immersion process, first perform alkaline pre -processing in lithium cloud mother, and then immerse them under acidic conditions, solve the problem of low lithium extraction efficiency in lithium and lithium. Lithium immersion effect.

CN119351783APending Publication Date: 2025-01-24HUNAN ARSENIC ENVIRONMENTAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411670454.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently extract lithium in low-quality and difficult to immerse lithium mica, and the traditional ignition process has problems such as high energy consumption and difficulty in treating exhaust gas.

Method used

Adopt a full wet method to strengthen the immersion process, first add sodium hydroxide or potassium hydroxide solution to the lithium cloud mother for enhanced pre -treatment, destroy the lithium cloud mother structure, dissolve some silicon and aluminum, reduce the consumption of fluoride, and then perform under acidic conditions under acidic conditions Immerse, finally to obtain lithium carbonate through excessive saturated sodium carbonate solution.

Benefits of technology

Increasing the lithium immersion rate, the lithium immersion rate can reach 98.5%, reducing the immersion temperature and time, reducing the impurities, and reducing the amount of fluoride, avoiding the problem of equipment corrosion and tail gas treatment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium resource extraction, and particularly relates to a method for intensively leaching lithium in low-grade refractory lepidolite through a full-wet method. The method comprises the following steps: S1, a strengthening step: adding alkali liquor into lepidolite according to a solid-to-liquid ratio of 1: (1-1.5), stirring and reacting at 20-30 DEG C for 2-3 hours, and then filtering to obtain strengthening liquid and strengthening slag; s2, acid leaching is conducted, specifically, an acidic material and an auxiliary agent are added into the reinforced slag, stirring reaction is conducted for 0.5-1.5 h at the temperature of 90-100 DEG C, and leaching liquid and leaching slag are obtained; and S3, lithium precipitation: adding an excessive saturated sodium carbonate solution into the leachate, reacting at 80-90 DEG C for 1-2 hours, and filtering to obtain lithium carbonate. According to the method disclosed by the invention, the step of strengthening pretreatment is added before leaching, so that low-grade and refractory lepidolite can be better destroyed, subsequent leaching is more facilitated, the leaching difficulty is reduced, and the leaching rate of lithium is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium resource leaching, and in particular relates to a method for strengthening the leaching of lithium from low-grade and difficult-to-leach lithium mica by a fully wet method. Background Art

[0002] Lepidolite is the most common lithium mineral and an important mineral for lithium extraction. It is a basic aluminum silicate of potassium and lithium and belongs to the mica mineral family. It is one of the main raw materials for extracting rare metal lithium. Lithium extraction from mica is mostly done by pyrometallurgical processes, which involve mixing mica with substances such as sodium sulfate, potassium sulfate, ammonium chloride, and fluoride, either alone or in combination, and then calcining at high temperature (800°C to 1200°C) and then leaching with water. These methods have high energy consumption and high environmental treatment costs.

[0003] Prior art CN103145158B discloses a method for preparing lithium carbonate from lithium mica by sulfuric acid roasting, which includes the following process flow: (1) roasting and defluorination; (2) cooling and grinding; (3) slurry adjustment; (4) low-temperature roasting; (5) leaching and separation; (6) impurity removal; (7) concentration; (8) freezing; (9) carbonization and precipitation of lithium to obtain lithium carbonate products. This process uses concentrated sulfuric acid roasting, the reaction temperature is 200-300°C, and the energy consumption is lower than that of the traditional salt method, but the acid consumption is large, the tail gas disposal is difficult, and there is air pollution.

[0004] Prior art CN 113684369 B relates to a method for treating waste industrial lithium-aluminum electrolytes, wherein fine powder of waste industrial lithium-aluminum electrolytes and a first reactant are mixed, roasted, and roasted materials are obtained; after water leaching, filtrate A and filter residue A are obtained; after adjusting the pH value of filtrate A to 6-10, cryolite products are obtained; a second acid solution and filter residue A are mixed, and after reaction, filtrate C and filter residue C are obtained; the pH value of filtrate C is adjusted to 6-8, and hydroxyaluminum fluoride products and filtrate C' are obtained; carbonate is added to filtrate C', and after reaction, lithium carbonate products are obtained. This invention is different from the traditional strong acid leaching of waste aluminum electrolytes. The sodium-liquid composite cryolite in the electrolyte is converted into LiAl2(OH)7 by alkali roasting treatment, and the separation of lithium elements from other impurities is realized simply and conveniently. The lithium recovery rate is high, and the by-product regenerated cryolite can be returned to the aluminum electrolytic cell for use, which further improves the utilization rate of other valuable elements and provides a new method for the recovery and treatment of lithium-aluminum electrolytes. However, this prior art also uses pyrolysis, which has the problems of high energy consumption and difficult tail gas treatment.

[0005] Subsequently, a wet lithium extraction process was developed, which does not require high-temperature roasting, but directly uses sulfuric acid or hydrochloric acid and auxiliary leaching agents to extract lithium. For example, Chinese invention patent ZL201010235150.2 discloses a method of using sulfuric acid and fluorine-containing compounds or minerals to decompose lithium mica, evaporate the residual acid, and then add water to extract lithium from lithium mica. However, this method consumes a lot of acid and releases a large amount of toxic gases, such as SO3, SO2, and SiF4.

[0006] Prior art CN201611206891.1 discloses a method for cyclic extraction of lithium using lepidolite as raw material, wherein lepidolite is subjected to fluorination and acidolysis using hydrochloric acid and sodium fluoride as acidolysis solution, and the leachate can directly purify the precipitated lithium, and the leached residue is filtered after leaching with sodium hydroxide, and the sodium fluoride obtained by decompression evaporation and crystallization of the filtrate can be re-entered into the lithium extraction cycle. However, hydrochloric acid or hydrofluoric acid is used in large amounts and is volatile, and is highly corrosive to equipment. Taking Example 3 as an example, the concentration of the hydrochloric acid solution is 10 mol / L, and the liquid-solid ratio thereof to lepidolite is 5.0:1, and 100 g of lepidolite residue requires about 417 mL of concentrated hydrochloric acid to configure the corresponding liquid-solid ratio, and the process control requirements are harsh.

[0007] Prior art CN117985741A discloses a comprehensive recycling method for lithium slag from lithium mica, comprising the following steps: (1) leaching with alkali; (2) precipitation with acid; (3) evaporation and concentration; (4) impurity removal with alkali; (5) lithium precipitation. The invention adopts a new idea to recover the valuable metal elements in lithium slag from lithium mica, effectively recovers the residual lithium, aluminum and potassium elements in the lithium slag from lithium mica, and has high economic value; the process flow and equipment involved in the invention are simple and the investment is low. However, this method requires two steps of precipitation and impurity removal, and the lithium recovery rate is low. Summary of the invention

[0008] The purpose of the present invention is to provide a method for strengthening the leaching of lithium from low-quality and difficult-to-leach lithium mica by a full wet method, so as to improve the leaching rate of lithium.

[0009] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is: A method for fully wet enhanced leaching of lithium from low-grade and difficult-to-leach lithium mica comprises the following steps: S1, strengthening step: crushing and grinding the lithium mica to a particle size of ≤0.15mm, adding sodium hydroxide solution or potassium hydroxide solution to the lithium mica at a solid-liquid ratio of 1:1-1.5, with a mass concentration of 40%-50%, stirring and reacting at 20-30°C for 2-3h, and then filtering to obtain a strengthening liquid and a strengthening slag; the chemical formula of the low-grade difficult-to-leach lithium mica is K{Li 2-x Al 1+x [Al 2x Si 4-2x O 10](OH,F)2}, where x=0~0.5, lithium mica contains Li2O 0.6-1.8%, Na2O 1.0-2.5%, Al2O3 20-23%, SiO2 45-50%, Fe2O3 0.2-0.5%, K2O 5.0-7.0%, CaO 2.0-2.5%, MgO 0.2-0.4%; S2. Acid leaching: adding acidic substances and additives to the strengthened slag, stirring and reacting at 90-100°C for 0.5-1.5h to obtain leaching solution and leaching slag; S3. Lithium precipitation: add excess saturated sodium carbonate solution to the leaching solution, react at 80-90°C for 1-2h, and filter to obtain lithium carbonate.

[0010] In a preferred embodiment, the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0011] In a preferred embodiment, the concentration of the alkali solution is 40%-50%.

[0012] In a preferred embodiment, the acidic substance is one or more of sulfuric acid, nitric acid and hydrochloric acid.

[0013] In a preferred embodiment, the auxiliary agent is one or more of sodium fluoride, potassium fluoride, lithium fluoride, rubidium fluoride, cesium fluoride, and hydrofluoric acid.

[0014] In one of the preferred embodiments, the volume mass ratio of the added amount of the acidic substance to the strengthened slag is 10-20 mL: 60-70 g.

[0015] In one preferred embodiment, the volume mass ratio of the additive added to the strengthened slag is 15-25 mL: 60-70 g.

[0016] In one preferred embodiment, before adding the acidic substance and the additive, water is added to the strengthened slag at a mass ratio of 1-2:1-2 to prepare a slag slurry.

[0017] The present invention is further explained and illustrated below. The lithium mica contains less than 0.5% single lithium, and it is difficult to extract all the lithium using the existing technology. The present invention is aimed at the difficult-to-leach lithium mica, and adds a strengthening pretreatment step before leaching, which can better destroy the lithium mica structure and dissolve part of silicon and aluminum. Silicon and aluminum will consume HF. Alkali is first used to destroy the lithium mica structure, dissolve part of silicon and aluminum, reduce the consumption of HF, and is more conducive to subsequent leaching, reducing the difficulty of leaching, and can be adapted to "low-quality difficult-to-leach" lithium mica, and improve the lithium leaching rate. The lithium leaching rate is as high as 98.5%, the leaching temperature is low, the leaching time is short, and the impurity content in the leachate is low.

[0018] Compared with the prior art, the advantages of the present invention are: 1. The present invention discloses a method for fully wet enhanced leaching of lithium from low-quality and difficult-to-leach lithium mica. An enhanced pretreatment step is added before leaching, which can better destroy the lithium mica, is more conducive to subsequent leaching, reduces the difficulty of leaching, can be adapted to "low-quality and difficult-to-leach" lithium mica, and improves the leaching rate of lithium. The lithium leaching rate is as high as 98.5%, the leaching temperature is low, and the leaching time is short.

[0019] 2. The present invention reduces the amount of fluoride used in the leaching step. The silicon and aluminum in the lepidolite will consume HF. The present invention strengthens the pretreatment step by first destroying the lepidolite structure with alkali, dissolving part of the silicon and aluminum, reducing the consumption of HF by silicon and aluminum, and reducing the amount of fluoride added in the leaching step. HF is particularly corrosive to equipment, volatilizes at high temperatures, and has high safety requirements for equipment. The present invention greatly reduces the amount of fluoride used. DETAILED DESCRIPTION

[0020] The detailed structure of the present invention is further described below in conjunction with specific implementation methods.

[0021] The low-quality and difficult-to-leach lithium mica of the present invention refers to: 2-x Al 1+x [Al 2x Si 4-2x O 10 ](OH,F)2}(x=0~0 .5), the main chemical components include: Li2O 0.96%, Na2O 2.1%, Al2O3 21.8%, SiO2 48.44%, Fe2O3 0.41%, K2O 6.7%, CaO 2.37%, MgO 0.37%. Example

[0022] A method for fully wet enhanced leaching of lithium from low-grade and difficult-to-leach lithium mica comprises the following steps: The lithium-containing mica was crushed and ground to a particle size of ≤0.15 mm, and a sodium hydroxide aqueous solution with a mass concentration of 40% was added according to a solid-liquid ratio of 1:1, and the temperature was controlled at 25°C. The reaction was carried out under stirring for 3 hours. During the process, water was appropriately added to maintain the reaction liquid-solid ratio. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain a pretreated liquid and a pretreated residue; The concentration of the slurry was adjusted according to the mass ratio of water to pretreated slag of 1:1. After stirring evenly, sulfuric acid and potassium fluoride were added. The volume mass ratio of sulfuric acid added to the strengthened slag was 15mL:65g. The volume mass ratio of hydrofluoric acid added to the strengthened slag was 20mL:65g. The temperature was controlled at 100°C and the reaction was carried out for 1h under stirring. Water was appropriately added during the process to maintain the liquid-solid ratio of the reaction. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain the leachate and leachate slag. The lithium leaching rate in the leachate was 98.5%.

[0023] Add excess saturated sodium carbonate solution to the leaching solution, react at 90°C for 1 hour, and filter to obtain lithium carbonate. Example

[0024] A method for fully wet enhanced leaching of lithium from low-grade and difficult-to-leach lithium mica comprises the following steps: The lithium-containing mica was crushed and ground to a particle size of ≤0.15 mm, and a sodium hydroxide aqueous solution with a mass concentration of 50% was added according to a solid-liquid ratio of 1:1, and the temperature was controlled at 30°C. The reaction was carried out under stirring for 2 hours. During the process, water was appropriately added to maintain the reaction liquid-solid ratio. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain a pretreated liquid and a pretreated residue; The concentration of the slurry was adjusted according to the mass ratio of water to pretreated slag of 1:1. After stirring evenly, sulfuric acid and potassium fluoride were added. The volume mass ratio of sulfuric acid added to the strengthened slag was 15mL:65g. The volume mass ratio of hydrofluoric acid added to the strengthened slag was 20mL:65g. The temperature was controlled at 90°C and the reaction was carried out for 1h under stirring. Water was appropriately added during the process to maintain the liquid-solid ratio of the reaction. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain the leachate and leachate slag. The lithium leaching rate in the leachate was 98.3%.

[0025] Add excess saturated sodium carbonate solution to the leaching solution, react at 90°C for 1 hour, and filter to obtain lithium carbonate.

[0026] Example 3

[0027] A method for fully wet enhanced leaching of lithium from low-grade and difficult-to-leach lithium mica comprises the following steps: The lithium-containing mica was crushed and ground to a particle size of ≤0.15 mm, and a potassium hydroxide aqueous solution with a mass concentration of 50% was added according to a solid-liquid ratio of 1:1.5, and the temperature was controlled at 20°C. The reaction was carried out under stirring for 3 hours. During the process, water was appropriately added to maintain the reaction liquid-solid ratio. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain a pretreated liquid and a pretreated residue; The concentration of the slurry was adjusted according to the mass ratio of water to pretreated slag of 1:2. After stirring evenly, sulfuric acid and potassium fluoride were added. The volume mass ratio of sulfuric acid added to the strengthened slag was 20mL:65g. The volume mass ratio of hydrofluoric acid added to the strengthened slag was 25mL:65g. The temperature was controlled at 95°C and the reaction was carried out for 1h under stirring. Water was appropriately added during the process to maintain the liquid-solid ratio of the reaction. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain the leachate and leachate slag. The lithium leaching rate in the leachate was 97.6%.

[0028] Add excess saturated sodium carbonate solution to the leaching solution, react at 85°C for 2h, and filter to obtain lithium carbonate.

[0029] Comparative Example 1 No intensive pre-treatment steps A method for leaching lithium from low-quality and difficult-to-leach lithium mica by a full wet method comprises the following steps: The lithium-containing mica was crushed and ground to a particle size of ≤0.15mm, water was added, and the pulp concentration was adjusted according to the mass ratio of water to pre-treated slag of 1:1. After stirring evenly, sulfuric acid and potassium fluoride were added. The volume mass ratio of sulfuric acid added to the strengthened slag was 15mL:65g. The volume mass ratio of hydrofluoric acid added to the strengthened slag was 20mL:65g. The temperature was controlled at 100℃, and the reaction was carried out for 1h under stirring conditions. Water was appropriately added during the process to maintain the liquid-solid ratio of the reaction. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain the leachate and leachate slag. The lithium leaching rate in the leachate was 72.6%. If the leaching rate needs to be increased, the amount of hydrofluoric acid and sulfuric acid needs to be greatly increased. For example, the amount of hydrofluoric acid and sulfuric acid was greatly increased to 2.5 times, and the lithium leaching rate in the leachate reached 80.2%.

[0030] Add excess saturated sodium carbonate solution to the leaching solution, react at 90°C for 1 hour, and filter to obtain lithium carbonate.

[0031] Comparative Example 2 Intensive pretreatment steps with additional substances A method for fully wet enhanced leaching of lithium from low-grade and difficult-to-leach lithium mica comprises the following steps: The lithium-containing mica was crushed and ground to a particle size of ≤0.15 mm, and a sodium carbonate aqueous solution with a mass concentration of 40% was added according to a solid-liquid ratio of 1:1, and the temperature was controlled at 25°C. The reaction was carried out under stirring for 3 hours. During the process, water was appropriately added to maintain the reaction liquid-solid ratio. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain a pretreated liquid and a pretreated residue; The concentration of the slurry was adjusted according to the mass ratio of water to pretreated slag of 1:1. After stirring evenly, sulfuric acid and potassium fluoride were added. The volume mass ratio of sulfuric acid added to the strengthened slag was 15mL:65g. The volume mass ratio of hydrofluoric acid added to the strengthened slag was 20mL:65g. The temperature was controlled at 100°C and the reaction was carried out for 1h under stirring. Water was appropriately added during the process to maintain the liquid-solid ratio of the reaction. After the reaction was completed, the liquid and solid were separated, and the filter cake was fully washed to obtain the leachate and leachate slag. The lithium leaching rate in the leachate was 80.1%.

[0032] Add excess saturated sodium carbonate solution to the leaching solution, react at 90°C for 1 hour, and filter to obtain lithium carbonate.

[0033] Comparative Example 3 Use the following process to treat low-quality, difficult-to-leach lepidolite: (1) Alkali leaching: For the crushed raw materials, add 2 mol / L sodium hydroxide solution at a solid-liquid ratio of 1:3, leaching at 60°C for 90 min, and filter to obtain the filtrate and residue; (2) Acid precipitation: adding sulfuric acid to the filtrate obtained in step (1), controlling the pH value at the reaction end point to be 3.5, filtering to obtain the filtrate and precipitate, wherein the precipitate is a silicic acid precipitate; (3) Evaporation and concentration: heating the filtrate obtained in step (2) to 90° C., evaporating and concentrating by 25 times, then cooling to 20° C., and filtering to obtain potassium sulfate precipitate and filtrate; (4) Adding alkali to remove impurities: adding sodium hydroxide to the filtrate obtained in step (3) under the condition that the reaction end point pH is 7, and filtering to obtain aluminum hydroxide precipitate and lithium-containing liquid phase; (5) Lithium precipitation: add excess saturated sodium carbonate solution to the lithium-containing liquid phase, react at 90°C for 1 hour, and filter to obtain lithium carbonate; the filtered liquid phase is returned to step (4) and used as a saturated sodium carbonate solution.

[0034] The yield of lithium carbonate was tested to be extremely low, only 0.81%. The filtrate of step (1) was tested and found to be mostly in the residue. This method (the method of the prior art) could not effectively extract lithium. The reason may be that the composition of the raw materials is different, which results in the inability to effectively extract lithium according to the method of the prior art.

[0035] Comparative Example 4 On the basis of Example 1, the concentration of sodium hydroxide was adjusted to 20%, and the rest was consistent with the Example. The results showed that the lithium leaching rate in the leaching solution was 57%.

[0036] Comparative Example 5 On the basis of Example 1, the concentration of sodium hydroxide was adjusted to 70%, and the rest was consistent with the Example. The results showed that the lithium leaching rate in the leaching solution was 66%.

[0037] Comparative Example 6 On the basis of Example 1, the temperature of the strengthening step was adjusted to 50° C., and the rest was consistent with the Example. The results showed that the lithium leaching rate in the leaching solution was 86%.

[0038] Comparative Example 7 On the basis of Example 1, no water was added to adjust the slurry concentration before adding sulfuric acid, and sulfuric acid and hydrofluoric acid were directly added, and the rest was consistent with the example. The results showed that the lithium leaching rate in the leachate was 61%.

[0039] The above is a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and concepts of the present invention, which should be covered by the protection scope of the claims of the present invention.

Claims

1. A method for fully wet enhanced leaching of lithium from low-quality and difficult-to-leach lithium mica, characterized in that: The following steps are involved: S1, strengthening step: crushing and grinding the lithium mica to a particle size of ≤0.15mm, adding sodium hydroxide solution or potassium hydroxide solution to the lithium mica at a solid-liquid ratio of 1:1-1.5, with a mass concentration of 40%-50%, stirring and reacting at 20-30°C for 2-3h, and then filtering to obtain a strengthening liquid and a strengthening slag; the chemical formula of the low-grade difficult-to-leach lithium mica is K{Li 2-x Al 1+x [Al 2x Si 4-2x O 10 ](OH,F)2}, where x=0~0.5, lithium mica contains Li2O 0.6-1.8%, Na2O 1.0-2.5%, Al2O3 20-23%, SiO245-50%, Fe2O3 0.2-0.5%, K2O 5.0-7.0%, CaO 2.0-2.5%, MgO 0.2-0.4%; S2. Acid leaching: adding acidic substances and additives to the strengthened slag, stirring and reacting at 90-100°C for 0.5-1.5h to obtain leaching solution and leaching slag; S3. Lithium precipitation: add excess saturated sodium carbonate solution to the leaching solution, react at 80-90°C for 1-2h, and filter to obtain lithium carbonate.

2. The method according to claim 1, characterized in that The acidic substance is one or more of sulfuric acid, nitric acid and hydrochloric acid.

3. The method according to claim 1, characterized in that The auxiliary agent is one or more of sodium fluoride, potassium fluoride, lithium fluoride, rubidium fluoride, cesium fluoride and hydrofluoric acid.

4. The method according to claim 1, characterized in that: The volume mass ratio of the added amount of the acidic substance to the strengthened slag is 10-20 mL: 60-70 g.

5. The method according to claim 1, characterized in that The volume mass ratio of the added amount of the auxiliary agent to the strengthened slag is 15-25mL:60-70g.

6. The method according to any one of claims 1 to 5, characterized in that: Before adding the acidic substance and the additive, water is added to the reinforced slag in a mass ratio of 1-2:1-2 to prepare a slag slurry.

Citation Information

Patent Citations

  • Process for extracting lithium from lithionite by fluorine chemistry

    CN101885496B

  • Method for preparing lithium carbonate from lepidolite through sulfuric acid roasting method

    CN103145158B

  • Method for circularly extracting lithium from lithium mica as raw material

    CN106673021A

  • A method for treating waste industrial lithium-containing aluminum electrolyte

    CN113684369B

  • Comprehensive recycling method of lepidolite lithium extraction slag

    CN117985741A

Cited By

  • Novel lithium extraction method and device for low-grade lepidolite

    CN121250134A